Gambaran tingkat kecemasan terhadap prosedur perawatan gigi pada mahasiswa di berbagai Program Studi Fakultas Kedokteran Universitas Udayana - Ni Putu Fitri Agustiari; Putu Ratna Kusumadewi Giri; Naomi Vembriati (School of Dentistry Faculty of Medicine Udayana University, 2018)
Background: Anxiety about dental procedures is a natural thing experienced by every individual. The development of anxiety about dental procedures occur between ages of 18 and 26 years old, which has considered as a college student. Medical student is already equipped with knowledge about oral health science, both basic science or more specific one. With enough knowledge, it is expected that medical students do not feel anxious when performing dental treatment. Aim: The aim of this study is to describe the level of anxiety about dental procedures to students in Medical Faculty, Udayana University. Method: This study is a quantitative descriptive study with cross-sectional approach. The 107 samples was obtained using simple random sampling. Data were collected by using The Corah Dental Anxiety Scale (CDAS) questionnaire to determine the level of knowledge, the level of anxiety and dental procedures that the student most-worried about. Results: The results showed that the student with high level of knowledge (80%) are likely to experience mild to moderate anxiety. Whereas student with low level of knowledge (20%) tend to experience up to severe anxiety. Women tend to be more anxious than men. Conclusion: Conclusions from this research is most student in Medical Faculty, Udayana University tend to feel anxious when performing dental treatments.